2011
DOI: 10.1111/j.1365-263x.2011.01159.x
|View full text |Cite
|
Sign up to set email alerts
|

Caries increment over 2 years in preschool children: a life course approach

Abstract: New caries development of Hong Kong preschool children was low. Children's feeding, snaking and brushing habits, and parents' education attainment were the significant predictors for new caries development of preschool children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 20 publications
0
39
0
4
Order By: Relevance
“…However, few longitudinal studies have described the incidence of ECC in China [13, 14]. Wong et al [14] stated that the mean caries increment over the 2 years of the children aged 3–4 years old from Hong Kong was 0.9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few longitudinal studies have described the incidence of ECC in China [13, 14]. Wong et al [14] stated that the mean caries increment over the 2 years of the children aged 3–4 years old from Hong Kong was 0.9.…”
Section: Introductionmentioning
confidence: 99%
“…However, few longitudinal studies have described the incidence of ECC in China [13, 14]. Wong et al [14] stated that the mean caries increment over the 2 years of the children aged 3–4 years old from Hong Kong was 0.9. Ghazal, T., et al [15] reported that the two-year incidence of ECC among 1-year-old African-American children in Alabama was 39.3% and the three-year incidence was 65.8%.…”
Section: Introductionmentioning
confidence: 99%
“…They recommended the negative binomial distribution for describing dental caries indices in populations recognizing, as did Böhning et al [1999] decades later, that caries counts tend to exhibit overdispersion, i.e., excess variation in them relative to the Poisson distribution. Subsequently, researchers [e.g., Syrjälä et al , 2003; Broffit et al 2007; Ismail et al , 2008; Maserejian et al 2008b; Thitasomakul et al , 2009; Wong, Lu and Lo, 2011] have often analyzed the effects of risk factors on dental caries indices using negative binomial regression [Hilbe, 2008]. …”
mentioning
confidence: 99%
“…The frequency of brushing is a protective factor for the development of dental caries. Several studies have associated a low frequency of brushing with the development of caries in the permanent dentition 13,16 . In this study, a frequency of two or more brushings per day functioned as a protective factor against the development of caries in the permanent dentition.…”
Section: Discussionmentioning
confidence: 99%
“…The American and Brazilian Associations of Pediatrics and Pediatric Dentistry recommend toothbrushing with fluoride toothpaste, beginning with the eruption of the first tooth. This promotes control of early childhood caries and does not produce an increase in the severity of fluorosis since the toothpaste is used in small quantities 16 .…”
Section: Discussionmentioning
confidence: 99%